2018
DOI: 10.1007/s10815-017-1109-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on the incidence and influences on heterotopic pregnancy from embryo transfer of fresh cycles and frozen-thawed cycles

Abstract: No significant difference in the incidence of heterotopic pregnancy in fresh IVF cycles vs. frozen-thawed cycles could be demonstrated in a large cohort of patients. The risk factors of HP included history of ectopic pregnancy and PID. The clinical outcome after heterotopic pregnancy appears to be favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
1
18
3
2
Order By: Relevance
“…We also found that a previous history of EP and endometriosis were independent risk factors for EP in IVF/ET, which was consistent with the findings from previous studies 27282930. These results suggest that careful monitoring is necessary during the IVF/ET cycles in women with these risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that a previous history of EP and endometriosis were independent risk factors for EP in IVF/ET, which was consistent with the findings from previous studies 27282930. These results suggest that careful monitoring is necessary during the IVF/ET cycles in women with these risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…2, where an infant with 10 months of age, scored 8 in social life ability scale). The median score of social maturity was 15 (range, [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found an obviously increased occurrence of heterotopic interstitial pregnancy in patients with a history of pelvic inflammatory disease or tubal operation, which was consistent with previous report. 13 Therefore, the patients with the above risk factors who underwent ART should be cautious about the occurrence of HP.…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers thought the supra physiologic hormonal levels could confer a higher ectopic pregnancy rate with fresh ET cycles (34,35). However, Xiao et al found no signi cant difference in ectopic pregnancy rate between fresh ET and FET (36). Chen et al found there was higher pregnancy loss rate in the fresh ET group compared to FET group in ovulatory women (13).…”
Section: Discussionmentioning
confidence: 99%